ACCOUNTING, FINANCIAL AND ADMINISTRATIVE INFORMATION AND ITS IMPACT ON THE ECONOMIC MANAGEMENT OF PUBLIC ENTITIES - Mauricio Jaimes Roa; Ismael Fernando Valencia Bustamante; Sonia Soler Grillo; Christian Xavier Proaño Piedra; Josue Canchari de la Cruz, Julio V. Pardavé Brancacho, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on the bibliographic production based on the study of the variables Accounting, Financial and Administrative Information and its incidence in the economic management of Public Entities in Latin America. The analyzed information was obtained thanks to a revision through the Search tool provided by the Scopus web page achieving the identification of a total of 67 publications which are organized by means of the main characteristics of the volume of publications, Year of Publication, Country of Origin, Area of Knowledge, Type of Publication. Similarly, the position of different authors with respect to the proposed topic was analyzed through a qualitative analysis of the information collected. The results show that, within the Latin American countries, Colombia is the one with the highest number of publications registered in Scopus with a total of 28 documents reported by Scopus during the period 2015-2020. The year within this period where more publications were made was 2020 when a total of 25 documents were reported. The area of knowledge that had the greatest contribution to scientific production was Business with 38 publications and 94% of the identified publications were Journal Articles.